Kilka uwag o pojęciu tożsamości = A Few Words about the Concept of Identity - Bugajski, Marian (1949 -) (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article refers to various definitions of the concept of identity, however, its purpose is not to define, because such attempts have been made several times both by linguists as well as by researchers of other disciplines. The objective of the paper is to focus attention on the fact that the concept itself comprises many aspects. The other goal of the paper is to encourage further discussion on the subject.
Keywords: tożsamość; tożsamość aktywna; tożsamość pasywna; tożsamość deliberatywna; memetyka; identyfikacja; samoidentyfikacja; język; językoznawstwo; językoznawstwo polskie